The acceptability of real‐time health monitoring among community participants with depression: A systematic review and meta‐analysis of the literature. Issue 9 (27th April 2020) - de Girolamo, Giovanni; Barattieri di San Pietro, Chiara; Bulgari, Viola; Dagani, Jessica; Ferrari, Clarissa; Hotopf, Matthew; Iannone, Giuseppe; Macis, Ambra; Matcham, Faith; Myin‐Germeys, Inez; Rintala, Aki; Simblett, Sara; et al.
Abstract: Background: The application of experience sampling method/ecological momentary assessment (ESM/EMA) methods to individuals with major depressive disorder (MDD) seems promising, but evidence about their acceptability is still unclear. The aim of this systematic review and meta‐analysis (registration number CRD42017060438) was to investigate the acceptability of ESM/EMA techniques for health monitoring in patients with MDD, by examining the dropout rate and related‐reasons, and to explore the effects of individual, methodological, and technical features on dropping out. Method: According to PRISMA guidelines, after leading a systematic search on major electronic databases, a structured process for selecting and collecting data was followed. Results: A total of 19 studies were included in the analyses. From results, it emerged a dropout rate of 3.6%. Our findings showed that the use of paper and pencil tools in combination with electronic devices, the time‐based sampling method, and not providing monetary incentives significantly increase the dropout rate of patients with MDD during ESM/EMA monitoring. Age, gender, depression severity, duration of monitoring, number of assessments each day, and number of questions did not affect dropout rate. Conclusions: The results of this systematic review may assist clinicians and researchers in planning, implementing, or evaluating the use of ESM/EMA to assess the health status of community‐based individuals with MDD.